Socio-economic Impact of Caste Based Organization in and out of that Caste in Lalitpur Metropolitan (Reference to Jyapu Society) (KIC International Journal of Social Science and Management, 2022)
Jayapu s are considered as first settlers of the Kathmandu valley but from the middle age they have been exploited and suppressed. Jyapu Society (Jyapu Samaj) was established in 1994 in Lalitpur Municipality comprising of 40 areas/toles and member population of around 70 thousand with the objective to uplift Jyapu community. This organization is working in the field of economic upliftment, education, health, cultural preservation, maintaining peace, security and discipline in the community, curtail unsuitable traditional behavioral, bring unity among Jyapu s and keep coordinated to other communities. In the descriptive study on impact of Jyapu society, the study finds 71% Jyapu s realize the economic benefits from Jyapu society but 30% non Jyapu s are skeptical about it. Therefore, Jyapu society must be cautious in its activities so it does not offend other communities.